A Study on Bilingual Verbal Fluency Task to Measure the Effect of Instruction in First and Second Language Performance - Pathak, Lekhnath Sharma; Rijal, Sabita (Nepalese Linguistics, 2022)
Verbal Fluency Task is a neuropsychological tool to measure lexical organization and retrieval in an individual. We used Phonetic Fluency Task and Semantic Fluency Task to study bilingual advantage in L1 (Nepali) and L2 (English) with two group of government school students with mean age of 14.46 years (SD 2.02 years). Participants were given 60 seconds each to create words from the given semantic category or letter/phonetic category. One group received instruction in L1 and another in L2. We found that the participants receiving instruction in L2 performed better even in L1 compared to the participants receiving instruction in L1.